Factors affecting the anthelmintic efficacy of cysteine proteinases against GI nematodes and their formulation for use in ruminants - Luoga, Wenceslaus (2013)
Gastrointestinal (GI) nematodes are important helminth pathogens responsible for severe losses to livestock industries and human health throughout the world. Control of these infections relies primarily on chemotherapy; however there is rapid development of resistance to all available classes of anthelmintic drugs, and therefore new alternative treatments are urgently required. Plant cysteine proteinases (CPs) from papaya latex, pineapple fruit and stem extracts have been demonstrated to be effective against GI nematodes of rodents, chickens, pigs and sheep. The current study extended evaluation of different plant extracts and the factors affecting the efficacy of papaya latex supernatant (PLS) as an anthelmintic against GI nematodes in a mouse model system and formulation and delivery for use in ruminants. The study started with purification and concentration of CPs in PLS using different methods to determine which of them would provide high yield of CPs. It was found that concentration by dialysis provided a high yield of active enzyme in PLS. Storage of PLS at -200C and -800C retained more active enzymes for prolonged period of time than at ambient temperature and 4oC. Motility assay conditions showed to have no influence on enzyme activity. While the in vitro experiment results showed significant detrimental effect of pineapple fruit extract, stem bromelain and little effect of kiwi fruit extract against Heligmosomoides bakeri motility. In vivo experiments showed less efficacy of these enzymes than expected when compared with PLS. The first factor to be assessed in this study was the effect of fasting on the anthelmintic efficacy of PLS. The results showed that PLS was equally effective in reducing worm burdens whether mice were fasted before treatment or not, and by avoiding fasting the side effects of treatment were minimized. Comparison of efficacy in a range of mouse strains indicated that efficacy varied between mice of different genotype. At the dose used, the treatment was most effective in C3H mice ranging from 90.5% to 99.3% in reducing worm burdens and less effective in NIHS, CD1 and BALB/c strains (7.9%, 36.0% and 40.5% reduction respectively). However, host sex and body size were shown not to have any influence on the anthelmintic efficacy of PLS. Since CPs are particularly sensitive to pH, variation between mouse strains in gut pH was investigated but no significant differences in pH were found along the GI tract of the poor (BALB/c) and high responder mice (C3H) to PLS treatment and concurrent administration of the antacid cimetidine also did not improve efficacy. The study also explored the potential of formulation and delivery of PLS as an anthelmintic drug for ruminants. In vitro studies involving both immediate and slow release dosage formulations simulating the physiological conditions (pH, temperature and peristaltic movement) in the GI tract of the animal were conducted. In the slow release experiments, two hydrophilic matrices were tested, the xanthan gum and hydroxypropyl methylcellulose (HPMC) (both Methocel-LVCR and Methocel-CR). Methocel-CR provided better slow release results compared to the others. In the immediate release experiments 3 disintegrants (Primojel, L-HPC and Ac-Di-sol) were investigated and Ac-Di-Sol® was found to produce the faster immediate drug release rate. Preliminary in vitro studies also showed that PLS was highly effective against equine GI nematodes. Finally the empirical findings in this study provide useful information for improvement of formulation and delivery of these naturally occurring plant-derived enzymes for treatment of intestinal worm infections in humans and livestock, while achieving maximum efficacy and minimal side-effects.